Psychometric Properties of Four Common Clinical Tests for Assessing Hamstring Flexibility in Young Adults - Liu, Hao; Shen, Ying; Xiong, Yuan; Zhou, Hongfei; Mao, Yuchen; Shen, Qiangqiang; Hong, Wenxia; Liu, Mingjian; Liu, Yanqian; Qiu, Li; Zhang, Zhijie; Jia, Yanbing (Frontiers in Physiology, 2022)
Objective: To examine the psychometric properties of four common hamstring muscle flexibility tests involving the straight leg raise (SLR), passive knee extension (PKE), sit and reach test (SRT) and toe touch test (TTT) in young adults. Methods: Forty-three young healthy adults (mean age 27.4 years) were recruited for 3 repeated sessions of hamstring flexibility assessments using the 4 tests mentioned above and the subsequent isokinetic examinations. The first two sessions (S1 and S2) were conducted by two different raters randomly on the first day (D1), and the third session (S3) was conducted by the same rater as S1 three days later (D4). The next day (D5), the isokinetic performances of knee extensors and flexors of the dominant leg were assessed. To evaluate the interrater (S1 vs S2) and test-retest (S1 vs S3) reliability of hamstring flexibility tests, intraclass correlation coefficients (ICCs), standard errors of measurement, and the minimum detectable differences were calculated. Correlation analyses were performed to study the association of each hamstring flexibility test with the isokinetic muscle function of the knee flexors (H) and extensors (Q), including the peak torque (PT), total amount of work (TW) and average power (AP). Results: Excellent interrater and test-retest reliability of hamstring flexibility tests involving the SLR, PKE, SRT and TTT were confirmed with ICCs ranging from 0.923 to 0.986. Fair correlations were found between the 4 hamstring flexibility tests and the H/Q for the PT at angular speeds of 180°/sec (Pearson’s r at 0.330 to 0.449). In addition, the PKE was fairly correlated with the AP of the hamstring (Pearson’s r =0.320) and the H/Q for the TW (Pearson’s r =0.345) and AP (Pearson’s r=0.386) at angular speeds of 180°/sec. Conclusions: This study confirmed that the SLR, PKE, SRT and TTT were reliable flexibility tests for hamstring muscles in young healthy adults, and the PKE might be a more valid outcome measure to predict hamstring injury.